Concept of Implant Placement in Deficient Posterior Maxillary Bone by Osseodensification Technique - Vivek Kolhe; Ashish G. Wawle; Milind V. Naphade; Nitin Adwani; Rajashree Gondhalekar (Dentistry and Medical Research)
Aim: The aim of this study was to analyze new bone formed after indirect sinus lift using Densah bur at 6 months and 1 year postoperatively. Materials and Methods: This study is a randomized control trial. Fifteen patients with edentulous deficient posterior maxilla were recruited for the surgery by osseodensification (OD) technique. This study enrolled healthy adults aged 18 and older, with good oral health, who required one or more dental implants in the posterior maxilla to support fixed rehabilitations such as single crowns or fixed partial prostheses. Inclusion criteria comprised individuals with sufficient buccopalatal width, a minimum of 3.5 mm residual bone height at the intended edentulous area, and an absence of diagnosed bone diseases or medications known to impact bone metabolism. Periotest was used for analysis. Results: At preoperative, residual bone height was only 5.65 (1.87) mm which increased to 12.13 (0.87) mm at postoperative immediate levels, and remained stable at 11.97 (0.85) mm at 6 months postoperative and at 11.4 (0.8) mm at 1-year postoperative. On overall comparison of bone measurements at different time intervals using repeated measures analysis of variance F-test, there was found to be highly statistically significant (P < 0.001) difference among overall comparison in relation to bone height. Conclusion: For the treatment of low-density edentulous areas, especially in individuals with osteoporosis, the OD technique involving the reversal of drilling direction is a reliable and straightforward method that does not necessitate specialized equipment.